2018
DOI: 10.1038/s41467-018-04706-7
|View full text |Cite
|
Sign up to set email alerts
|

NEK7 regulates dendrite morphogenesis in neurons via Eg5-dependent microtubule stabilization

Abstract: Organization of microtubules into ordered arrays is best understood in mitotic systems, but remains poorly characterized in postmitotic cells such as neurons. By analyzing the cycling cell microtubule cytoskeleton proteome through expression profiling and targeted RNAi screening for candidates with roles in neurons, we have identified the mitotic kinase NEK7. We show that NEK7 regulates dendrite morphogenesis in vitro and in vivo. NEK7 kinase activity is required for dendrite growth and branching, as well as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 68 publications
(97 reference statements)
5
35
0
Order By: Relevance
“…Although the mechanism for microtubule stabilization remains to be determined, we found that inhibition of the microtubule-based kinesin motor Eg5 with STLC also blocked this morphological change ( Fig. 1F), in line with recent reports that Eg5 promotes microtubule stabilization in post-mitotic neurons 34 . Hence, activation of NEK9 leads to a microtubuledependent change in interphase cell morphology characterised by formation of elongated cytoplasmic protrusions that contain both actin and stabilised microtubules.…”
Section: Constitutively Active Nek9 Leads To Microtubule-dependent Chsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the mechanism for microtubule stabilization remains to be determined, we found that inhibition of the microtubule-based kinesin motor Eg5 with STLC also blocked this morphological change ( Fig. 1F), in line with recent reports that Eg5 promotes microtubule stabilization in post-mitotic neurons 34 . Hence, activation of NEK9 leads to a microtubuledependent change in interphase cell morphology characterised by formation of elongated cytoplasmic protrusions that contain both actin and stabilised microtubules.…”
Section: Constitutively Active Nek9 Leads To Microtubule-dependent Chsupporting
confidence: 92%
“…Of particular interest to our findings, a kinasedependent role was recently described for NEK7 in stimulating dendrite growth in post-mitotic neurons. This resulted from phosphorylation by NEK7 of the kinesin motor protein Eg5, which in turn led to stabilization of microtubules 34 . Supporting a similar mechanism of action in cancer cells, we found that Eg5 was required for the altered cell morphology induced by activated NEK9.…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic study found that NEK7 was upregulated in differentiating neurons [157]. Curiously, downregulation of NEK7 expression was shown to lead to defects during neuron differentiation.…”
Section: Nek7mentioning
confidence: 99%
“…Recently, Nek7 has been found to be essential for MT nucleation (Kim et al, 2007), MT stabilization through Eg5 (Freixo et al, 2018), and to play a role in MT stability and dynamics (Cohen et al, 2013). The authors showed that Nek7 increases the growth and depolymerization velocity of MT and lengthens time of catastrophe.…”
Section: Discussionmentioning
confidence: 99%